1999
DOI: 10.4049/jimmunol.162.4.2281
|View full text |Cite
|
Sign up to set email alerts
|

The β-Glucan-Binding Lectin Site of Mouse CR3 (CD11b/CD18) and Its Function in Generating a Primed State of the Receptor That Mediates Cytotoxic Activation in Response to iC3b-Opsonized Target Cells

Abstract: Mouse leukocyte CR3 (Mac-1, αMβ2 integrin) was shown to function as a receptor for β-glucans in the same way as human CR3. Soluble zymosan polysaccharide (SZP) or pure β-glucans labeled with FITC or 125I bound in a saturable and reversible manner to neutrophils, macrophages, and NK cells. This lectin activity was blocked by anti-CD11b mAb M1/70 or 5C6 and did not occur with leukocytes from CR3−/− (CD11b-deficient) mice. SZP preparations containing primarily mannose or glucose bound to CR3, and the binding of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In addition to CD11b/CD18 glycosylation effecting functional outcomes, previous work has demonstrated that CD11b binding to fucosylated glycans regulates PMN epithelial adhesive interactions in the intestine ( 52 , 67 ). Interestingly these data highlight that PMN CD11b/CD18 can act both as a ligand for carbohydrate binding proteins and as a lectin-like mediator that can itself engage glycans to effect regulation of cellular functions ( 68 , 69 ). Interestingly, in contrast to inhibitory effects observed for degranulation and superoxide release, increased levels of PMN phagocytosis were observed downstream of sialidase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CD11b/CD18 glycosylation effecting functional outcomes, previous work has demonstrated that CD11b binding to fucosylated glycans regulates PMN epithelial adhesive interactions in the intestine ( 52 , 67 ). Interestingly these data highlight that PMN CD11b/CD18 can act both as a ligand for carbohydrate binding proteins and as a lectin-like mediator that can itself engage glycans to effect regulation of cellular functions ( 68 , 69 ). Interestingly, in contrast to inhibitory effects observed for degranulation and superoxide release, increased levels of PMN phagocytosis were observed downstream of sialidase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates the findings of Song et al., 16 where the CGD neutrophil production of LTB 4 was dependent on cell density. While a search for CD11b ligands proved unproductive, β-glucan, a major component of zymosan particles, has also been shown to bind to CD11b 52 and is still a possibility. Although we did not find a requirement for zymosan particles as a nidus for forming aggregates in live cell time-lapse imaging experiments, it is possible that β-glucan freed from zymosan particles is bound by CD11b and propagates inflammatory signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, neutrophils undergo priming for transmigration into the injured or infected tissue. Classical rolling/adhesion markers of neutrophil migration CD11b (also known as MAC-1) and CD62L (also known as L-selectin) are included in the panel to assess the migratory state [43,44]. In addition, primary and secondary granule exocytosis following migration can be determined by measuring the surface expression of CD63 and CD66b, respectively [45][46][47][48].…”
Section: Methodsmentioning
confidence: 99%